Soeharto : The Life And Legacy Of Indonesia's Second President (Ed. Bahasa Indonesia) - ABDULGANI-KNAPP, Retnowati (Kata Hasta Pustaka, 2007)
Soeharto : The Life And Legacy Of Indonesia's Second President...